Perbandingan Tingkat Pelaksanaan Praktik Kerja Industri SMKN 2 Purwodadi dan SMK Pembangunan Nasional di Purwodadi - Diana Langgeng Mustikawati; Fahmy Zuhda Bahtiar; Miftah Al Hafidz; Nurul Burhan (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2023)
The purpose of this research was to describe the process of the implementation of student state Vocational School Prakerin in Purwodadi and test the difference Prakerin in state Vocational School and private Vocational Schools in Purwodadi. This research uses research survey that is descriptive. The population of this research is the grade I Concrete Masonry Construction Engineering (TKBB) of state Vocational School and private vocational schools in Purwodadi. The Sampling technique used was Simple Random Sampling. The results of the research implementation process of state Vocational School that is as much as 10 students (21.74%) stated the very high category, 31 students (67.39%) including the categories high, by as much as 5 students (10.87%) stated the categories and score an average of 141.26. Results of the study in private vocational schools show that as many as 8 students (17.39%) including the very high category, 14 students (30.43%) said the high category, as many as 14 students (30.43%) including categories and score an average of 134.37. The results of calculation using SPSS t-Test of can to score t of extent and significance is 3.794 0.000 < 0.05 so the hypothesis described there are differences in the implementation process state Vocational School and private Vocational Schools in Purwodadi was supported by the data. Implementation of students state Vocational School Prakerin including categories higher and private Vocational Schools categories include enough.